The Prevalence of OSMF among Biscuit Factory Workers in Delhi NCR Region: A Cross-Sectional Study - Khateeb Khan; Mansimranjit Kaur Uppal; Saloni Deol Jain (International Healthcare Research Journal, 2018)
INTRODUCTION: The consumption of tobacco and related products is on the rise and promotes various medical/oral conditions that leads to increased morbidity/mortality in people.AIM: To assess the prevalence of Oral Submucous Fibrosis (OSMF) among biscuit factory workers in Delhi NCR region, IndiaMATERIALS AND METHOD: A total of 496 biscuit factory workers in Delhi NCR region, were interviewed and examined for OSMF and associated lesions with the help of a preformed, pre-tested questionnaire. The population was divided into four stratas according to age(≤34 years, 35- 44 years, 45-60 years and >60 years). Data was entered into Microsoft Excel. Descriptive statistics were applied and statistics (t-test) was done using SPSS 19.0.RESULTS: OSMF was observed in 173(34.9%)[ males 116 (23.4%), females 57(11.5%)] and the difference was statistically significant (p=0.02). The majority of subjects having OSMF (48, 27.8%) were seen in the age group of ≤34 years. Male: Female predilection was observed as 2.03CONCLUSION: Efforts and strategies need to be directed to reduce the overall consumption of tobacco and related products in both urban and rural areas.